Pengaruh Proteksi Awig-Awig, Whistleblowing Dan Efektivitas Pengendalian Internal Terhadap Pencegahan Kecurangan Pada LPD Di Kabupaten Tabanan - Ni Made Suci Ari Ayu Riantini; Made Arie Wahyuni (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2025)
This study aims to determine the effect of awig-awig protection, whistleblowing, and the effectiveness of internal control on fraud prevention at Village Credit Institutions in Tabanan Regency. This study is quantitative research. The population of this study is all Village Credit Institutions that are still operating in Tabanan Regency. The sampling technique in this study uses a purposive sampling method using the criteria of the Village Credit Institution which is in the healthy category. The number of samples in this study was 65 LPD with 130 LPD chairman and treasurer respondents. The data collection method in this research uses primary data obtained from distributing questionnaires to respondents which are then measured using a Likert Scale. The theory used is agency theory and the latest theory about fraud, namely the fraud hexagon theory. The data analysis technique used in study uses (1) descriptive statistical analysis, (2) data quality testing, namely using validity and reliability tests, (3) classical assumption testing, namely using normality, multicollinearity and heteroscedasticity tests, (4) hypothesis testing, namely multiple linear analysis, t testing and coefficient of determination testing with the SPSS 26.0 for windows program. The results of this study state that (1) awig-awig protection has a positive and significant effect on preventing fraud at Village Credit Institutions in Tabanan Regency. (2) whistleblowing has no significant effect on preventing fraud at Village Credit Institutions in Tabanan Regency. (3) the effectiveness of internal controls has a positive and significant effect on preventing fraud at Village Credit Institutions in Tabanan Regency. The coefficient of determination test state that the variables awig-awig protection, whistleblowing and internal control effectiveness are able to explain 33.1% of fraud prevention in LPD, while 66.9% are influenced by other factors.